Check
whether (2x+1)(3x+1)=2(x-1)(x-2)
is quadratic equation or
not?
Answers
Answered by
3
Step-by-step explanation:
(2x+1)(3x+1)=2(x-1)(x-2)
=2x.(3x+1)+1.(3x+1)=2.{x.(x-2)-1.(x-2)}
=6x^2+2x+3x+1=2.(x^2-2x-x+2)
=6x^2+5x+1=2.(x^2-3x+2)
=6x^2+5x+1=2x^2-6x+4
=6x^2-2x^2+5x+6x+1-4=0
=4x^2+11x-3=0
Similar questions
Physics,
2 months ago
Physics,
2 months ago
Geography,
2 months ago
Math,
4 months ago
English,
4 months ago
Social Sciences,
11 months ago
Social Sciences,
11 months ago
English,
11 months ago